Classics and comics - Kovacs, George, 1976-; Marshall, C. W., 1968- (Oxford University Press, 2011)
"Since at least 1939, when daily-strip caveman Alley Oop time-traveled to the Trojan War, comics have been drawing (on) material from Greek and Roman myth, literature and history. At times the connection is cosmetic-as perhaps with Wonder Woman's Amazonian heritage-and at times it is almost irrelevant-as with Hercules' starfaring adventures in the 1982 Marvel miniseries. But all of these make implicit or explicit claims about the place of classics in modern literary culture. Classics and Comics is the first book to explore the engagement of classics with the epitome of modern popular literature."-- Resumé vydavatele
Keywords: komiksy; umělecká literatura; literární vlivy; literárněvědné rozbory; comics; belles-lettres; literary influences; literary criticism and history; kolektivní monografie; elektronické knihy; collective monographs; electronic books